A meta-analysis comparing the effectiveness and safety of repetitive transcranial magnetic stimulation versus theta burst stimulation for treatment-resistant depression - Tao, Xiao; Jing, Zheng Wen; Yuan, Wang Kui; Yun, Guo Hui; Fang, Xie Jian; Sheng, Liao Ming (Frontiers in Psychiatry, 2025)
ObjectiveThis study compares the safety and effectiveness of theta-burst stimulation (TBS) and repetitive transcranial magnetic stimulation (rTMS) for treating treatment-resistant depression (TRD).MethodsWe reviewed randomized controlled trials (RCTs) that evaluated rTMS and TBS in managing TRD. Searches were conducted in PubMed, Embase, the Cochrane Library, and Web of Science for studies published up to July 31, 2024. Data from these studies were analyzed using statistical software.ResultsFive RCTs involving 1,196 patients were included, with 553 receiving rTMS and 663 receiving TBS. The analysis found no significant differences between rTMS and TBS in reducing depression [SMD = -0.07, 95% CI (-0.19, 0.04)] or anxiety [SMD = -0.02, 95% CI (-0.15, 0.11)], nor in side effects like headaches [OR = 1.00, 95% CI (0.72, 1.40)], nausea [OR = 1.42, 95% CI (0.79, 2.54)], or fatigue [OR = 0.87, 95% CI (0.46, 1.64)].ConclusionsBoth rTMS and TBS are similarly effective in reducing depression and anxiety symptoms, with comparable side effect profiles. However, TBS is more time-efficient, with sessions lasting only 192 seconds, making it a cost-effective option for patients. These findings support TBS as a practical treatment choice for TRD.